2017
DOI: 10.1128/aac.00688-17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Binuclear Cyclopalladated Compound Therapy for Cutaneous Leishmaniasis in the Murine Model of Infection with Leishmania amazonensis and Its Inhibitory Effect on Topoisomerase 1B

Abstract: Leishmaniasis is a disease found throughout the (sub)tropical parts of the world caused by protozoan parasites of the Leishmania genus. Despite the numerous problems associated with existing treatments, pharmaceutical companies continue to neglect the development of better ones. The high toxicity of current drugs combined with emerging resistance makes the discovery of new therapeutic alternatives urgent. We report here the evaluation of a binuclear cyclopalladated complex containing Pd(II) and N,N′-dimethylbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Treatment with 3.5 and 7 mg/kg of DPPE 1.1 led to a reduction of parasite load in foot lesions of 93 and 99%, respectively. In comparison with in vivo treatment with CP2, our data indicate the higher efficacy of DPPE 1.1 over this cyclopalladated compound since at the same concentration (7 mg/kg) mice treated with DPPE 1.1 and CP2 displayed a decrease of parasite load of 99 and 55%, respectively ( Velásquez et al, 2017 ). Furthermore, treatment with DPPE 1.1 did not result in toxicity in L. (L.) amazonensis -infected BALB/c mice as demonstrated by hepatic and renal assays after treatment with this compound, corroborating literature data that showed the low toxicity of these palladacycle complexes in the treatment of mice against tumor cells ( Rodrigues et al, 2003 ).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Treatment with 3.5 and 7 mg/kg of DPPE 1.1 led to a reduction of parasite load in foot lesions of 93 and 99%, respectively. In comparison with in vivo treatment with CP2, our data indicate the higher efficacy of DPPE 1.1 over this cyclopalladated compound since at the same concentration (7 mg/kg) mice treated with DPPE 1.1 and CP2 displayed a decrease of parasite load of 99 and 55%, respectively ( Velásquez et al, 2017 ). Furthermore, treatment with DPPE 1.1 did not result in toxicity in L. (L.) amazonensis -infected BALB/c mice as demonstrated by hepatic and renal assays after treatment with this compound, corroborating literature data that showed the low toxicity of these palladacycle complexes in the treatment of mice against tumor cells ( Rodrigues et al, 2003 ).…”
Section: Discussionmentioning
confidence: 85%
“…Other palladacycles were tested against Leishmania and showed an effective activity only on promastigote growth ( Fricker et al, 2008 ) and previous data from our group showed the in vitro and in vivo efficacy of the palladacycle complex DPPE 1.2 on L. (L.) amazonensis ( Paladi et al, 2012 ). More recently the leishmanicidal activity of a series of palladacycles on intracellular amastigotes of L. (L.) amazonensis was also demonstrated and among them a binuclear palladacycle complex named CP2 showed an effective action on L. (L.) amazonensis infection ( Velásquez et al, 2016 , 2017 ). The leishmanicidal activity of DPPE 1.1 is comparable to that observed with CP2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the aforementioned findings, and as a part of our continuing research program in the field of coordination and biological chemistry of Pd(II) complexes, [16][17][18][19][20][21] we present herein the synthesis, characterization and cytotoxic evaluation of the compounds [PdL 2 (tm-biimH 2 )]Cl 2 ·nH 2 O, where L is thiourea (2), N-methylthiourea (3), N-phenylthiourea (4), N,N'-dimethylthiourea (5), N,N'-diphenylthiourea (6); n = 3-5; tmbiimH 2 is 2,2'-bis(4,5-dimethylimidazole).…”
Section: Introductionmentioning
confidence: 99%
“…For quantitative PCR assays, we used mouse peritoneal macrophages collected from adult male Swiss albino mice, infected with L. infantum as previously described ( Velásquez et al 2017 ), except that the assay was performed in 25-cm 2 cell culture flasks (Nunc™, Roskilde, Denmark). These assays were approved by the Ethics Committee for Animal Experimentation (Protocol CEUA/FCF/CAr no.…”
mentioning
confidence: 99%